RETRACTED: Methodological features of the development of intelligent information technology for the transportation process in railway transport - Smirnov F.A.; Novichikhin A.V.; Kovalev K.E. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001